The Influence of Palliative Care Guidance in Physical Aspects in Families on Level of Independence Post-Stroke Patients' Families in Garut Regency - Zahara Farhan; Rudi Alfiansyah; Devi Ratnasari; Angga Dipa Nagara; Eti Suliyawati (Jurnal Penelitian Pendidikan IPA, 2023)
Physical complications due to stroke result in a decrease in the patient's level of independence to meet their daily needs, so it is necessary to carry out rehabilitation measures to increase independence through providing palliative care guidance at home. The aim of this research is to determine effect of palliative care guidance in physical aspect on the level of independence of families of post-stroke patients in Garut Regency. This research method is quasi experimental with one group pre-test and post-test design. The research sample was families who had family members with stroke infarction, 20 respondents in intervention group, sampling technique used purposive sampling. Data collection used standard nursing operational procedures from PPNI and family independence level instruments. Data analysis used Wilcoxon. The results of the research before being given palliative care guidance in the physical aspect, most families (55%) were at level 2 of independence and after providing palliative care guidance most of the families (55%) were at level 3 of independence. There was an influence of palliative care guidance in the physical aspect on level of independence of post-stroke patients' families with p value of 0.00. Providing information and skills through palliative care guidance can increase family understanding and independence in caring for family members who have experienced a stroke, so that palliative services can be used as one of the health center's work programs to improve quality of life for stroke infarction patients.